Menyingkap Rahasia di Balik Runtuhnya Lembaga Keuangan Mikro ‘Bertopeng’ Syariah - Agus Arifin; Lilik Purwanti; Yeney Widya Prihatiningtias (University of Merdeka Malang, 2018)
This study aims to explain the reasons behind the bankruptcy of BMT (Baitul Maal Wat Tanwil) PSU Malang with case study approach. The data are collected through documentation and interviews. The interviews are conducted on five informans namely informan A, B, C, D and E. The results show that the bankruptcy of BMT PSU is caused by internal factors and external factors. Internal factors causing bankruptcy of BMT PSU are: unproductive fund management, bad credit (financing), fraud by employees, business loss, too high percentage of profit sharing, lack of good corporate governance (GCG) and weak internal control. Externals include: lack of security guarantees on customers' funds, economic pressures, lack of supervision and guidance from relevant agencies, as well as the onslaught of stronger new competitors. The findings of this research related to the causes of the bankruptcy BMT PSU, is expected to be useful for practitioners and the government in preparing strategies for strengthening BMT in the future.https://doi.org/10.26905/jmdk.v6i2.2240